"To Rise from the Darkest Ignorance": Black Texans' Engagement with the Politics of Racial Uplift. (2nd September 2021) - Lee, Nedra K.
ABSTRACT: Black newspapers are an important yet underused source for historically contextualizing African American sites. The Black press helped shape notions of African American identity and community through philosophies of racial uplift that promoted a vision of Black achievement and citizenship. Although sociologist E. Franklin Frazier criticized the Black press as elitist, I suggest that non-affluent African Americans were also invested in tenets of racial uplift. To demonstrate this, I examine five Black Texas newspapers and oral histories in conjunction with artifacts recovered from the Ransom and Sarah Williams Farmstead, a postbellum site in Travis County, Texas. The evidence suggests that emancipated Blacks, even in seemingly remote rural communities, mobilized around principles of racial uplift through education, consumer behavior, and religious devotion. I use the newspapers to contextualize the archaeological evidence and highlight the overlaps between messages of racial uplift in the Black press and the actions of the Williams family.